Concrete-Defect Detection Using New Ultrasonic Array - Farah Aina Jamal Mohamad; Ruzairi Abdul Rahim; Nasarudin Ahmad; Sallehuddin Ibrahim; Mohd Hafiz Fazalul Rahiman; Nur Arina Hazwani Samsun Zaini; Navintiran Rajan; Juliza Jamaludin (Penerbit UTM Press, 2024)
Indexed by MyCite